Capturing Carbon Dioxide from Industrial Waste Gases - Başaran, Özcan; Kirim, Yavuz (Fırat University, 2026)
In this study, the capture of CO2 released from an industrial production facility located between the provinces of Batman and Siirt using suitable solutions was modelled using the Aspen Plus simulation. In the study, a methyldiethanolamine (MDEA) solution was chosen as the CO2 capture agent. The process design utilized absorbers, strippers, heat exchangers, flash evaporators, and recirculation loops; different feed rates and tray counts were tested. In the first stage, only 47% of the CO2 could be captured with a feed solution of 400 t/h. However, by increasing the solution flow rate to 832 t/h, approximately 72.14 t/h (95%) of the 76 t/h of CO2 present in the feed stream was successfully captured. Furthermore, it was observed that the number of trays, initially set at 30 in both the absorber and stripper, could be reduced to 21 without any significant change in performance, thereby increasing the cost-effectiveness of the process. The results obtained demonstrate that the CO2 capture method using MDEA solutions in industrial facilities provides high efficiency. However, it is emphasized that CO2 should not only be captured but also utilized in chemical/fuel production. The widespread adoption of such technologies will significantly contribute to Turkey's achievement of future climate goals.

Bu çalışmada, Batman ve Siirt illeri arasında bulunan bir endüstriyel üretim tesisinden salınan CO?'nin uygun çözümler kullanılarak yakalanması, Aspen Plus simülasyonu kullanılarak modellenmiştir. Çalışmada, CO? yakalama ajanı olarak metildietanolamin (MDEA) çözeltisi seçilmiştir. Proses tasarımında emiciler, sıyırıcılar, ısı eşanjörleri, flaş buharlaştırıcılar ve devridaim döngüleri kullanılmıştır; farklı besleme hızları ve tepsi sayıları test edilmiştir. İlk aşamada, 400 ton/saat besleme çözeltisi ile CO?'nin sadece %47'si yakalanabilmiştir. Ancak, çözelti akış hızı 832 ton/saate çıkarılınca, besleme akışında bulunan 76 ton/saat CO?'nin yaklaşık 72,14 ton/saati (%95) başarıyla yakalanmıştır. Ayrıca, başlangıçta hem emici hem de sıyırıcıda 30 olarak ayarlanan tepsi sayısının, performansta önemli bir değişiklik olmaksızın 21'e düşürülebileceği ve böylece işlemin maliyet etkinliğinin artırılabileceği gözlemlenmiştir. Elde edilen sonuçlar, endüstriyel tesislerde MDEA çözeltileri kullanılarak CO? yakalama yönteminin yüksek verimlilik sağladığını göstermektedir. Ancak, CO?'nin sadece yakalanması değil, kimyasal/yakıt üretiminde de kullanılması gerektiği vurgulanmaktadır. Bu tür teknolojilerin yaygın olarak benimsenmesi, Türkiye'nin gelecekteki iklim hedeflerine ulaşmasına önemli ölçüde katkıda bulunacaktır.
Endüstriyel Atık Gazlardan Karbon Dioksitin Yakalanması